KARAKTERISTIK KUANTITATIF DAN KUALITATIF KAMBING DAN DOMBA SEBAGAI HEWAN QURBAN DI MITRA TANI FARM - Komariah (Komariah); Dwi Joko Setyono; Aslimah (Aslimah) (Faculty of Animal Science, Universitas Gadjah Mada, 2015)
The objective of the present study was to study the qualitative characteristics (wool color, horned) and the quantitative characteristics (body weight, chest circumference, body length, age) of sheep and goats for qurban in the Mitra Tani Farm; and the consumers preferences of choosing the sheep and goat required for ‘qurban’ event. In total eighty three Jawarandu goats; 16 Garut; 37 Thin-Tailed and 35 Fat-Tailed rams were observed to measure their body weight, chest circumference, body length, age, the present of horn and hair color. Qualitative data was obtained by interviewing the owner and consumers of MT Farm (30 trader and 30 consumers). The data was statistically analysis using, chi-square test, correlation test and T test. The results showed that the consumers from Jakarta, Depok and Tangerang significantly (P<0.05) prefer goats than rams, while the consumers from Bogor, Yogyakarta and Bandung prefer rams than goats. The traders more consider the weight of the body (posture) and the price, while consumers more consider the finance budget. The average body weight of Jawarandu was 25.84±4.54 kg; Garut, Fat-Tailed and Thin-Tailed rams were 29.32±3.61, 28.45±5.54 and 28.44±4.65 kg respectively. The chest girth had higher correlation with body weight than body length. The percentage of goats and rams age were 60.56% (I0), 33.89% (I1) and 5.56% (I2). The dominant color of Jawarandu goat were brown (54.2%), black (26.51%) and white (19.28%). The color of Fat-Tailed rams wool more uniform than Thin-Tailed rams or Garut.(Key words: Characteristics of Sheep and Goat, Mitra Tani Farm, Qurban)